Considering a non-document: concepts, components, and contexts. Issue 3 (13th May 2019) - Kosciejew, Marc Richard Hugh
Abstract : Purpose: The purpose of this paper is to begin a conversation about the term "nondocument." It analyzes this term's possible concepts, components and contexts. Design/methodology/approach: This conceptual paper draws upon the work of documentation studies scholars, including Michael Buckland, Bernd Frohmann and Niels Windfeld Lund, to begin an exploration of the term "nondocument, " framed within the context of the 2013–2014 Israeli–Palestinian peace negotiations brokered by the USA. It is comprised of seven sections revolving around different questions regarding non-document. Findings: The document at the center of the 2013–2014 Israeli–Palestinian peace negotiations aimed to establish a framework for an eventual final-status peace agreement. There was skepticism, however, about the document's proposed reservations inscription permitting either party to express reservations with any part of the framework. It was claimed that this reservation inscription made the document self-negating and therefore a non-document. This document was arguably a hybrid entity: a document-non-document. It was a document in the context of the negotiations. It became a non-document in the context of the collapse of the negotiations. Research limitations/implications: The 2013–2014 peace negotiations between Israel and Palestine, brokered by the USA, revolved around a diplomatic document outlining provisions for a final peace settlement. The two parties were skeptical of a proposed provision permitting reservations to be expressed over other provisions within the document. An official involved in the negotiations stated that this provision made the document a non-document. But what exactly is meant by this term? This paper takes the opportunity to begin exploring such a notion. The aim, however, is not to definitively define non-document but instead to raise questions and provoke further discussions of this term. Originality/value: The concept of non-document is underdeveloped. This paper presents questions and conceptual tools to help develop this term whilst providing possible points of departure for further examinations of how documents are or might be non-documents. These questions and tools also point in directions for various other approaches to phenomena that could be regarded as documents in some respects but not in others, or the ways in which something could is "almost" but "not quite" a document, or even help determine what is "not document." Ultimately, this term could help expand other "conventional" approaches to documentation.